Olhares para as políticas linguísticas no Município de Itaiópolis/SC: entre o in vivo e o in vitro - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2015)
This study aims to discuss the relations between language and identity taking into consideration some of the language policies employed in the city of Itaiópolis/SC, where many Polish, Ukrainian and German immigrants live in contact with a native Indian tribe, which represents a multilingual and multicultural context. It seems important to emphasize that our research focuses on the Polish language, once the city is legally recognized as the Polish Culture Capital in the State. Thus, two projects related to the Polish language in development were observed: the Polish Language teaching project offered by the Catholic Church in the city and the interchange project developed in one of the city State schools, in order to discuss how the in vivo policies are related to the in vitro (CALVET, 2002, 2007) ones. Since the projects have been developed in distinct places, the role of the Catholic Church and the State school in relation to the continuity of the Polish Language Use and other Polish cultural practices is also addressed. The methodology employed is qualitative (OLIVEIRA, M., 2007), and the analysis gathers data obtained through observations, whose impressions were registered in a field diary, interviews and documental analysis. The research participants were teachers and students who took part in the relevant projects, besides members of the community that were involved with discussions regarding the language policies used in the city, totaling eight people. The theoretical background was supported with the Applied Linguistics contributions (MOITA LOPES, 2006, 2013; FABRÍCIO, 2006), from which the following themes were approached: multilingualism in Brazil (OLIVEIRA, G., 2009; MAHER, 2013), language policy and language teaching (CALVET, 2007; RAJAGOPALAN, 2013), language policies related to the Polish language (WACHOWICZ, 2002), the monolingualism myth creation (ALTENHOFEN, 2003, 2013; PINTO, 2014), and language, identity and culture (WOODWARD, 2000; HALL, 2000, 2006; SILVA, 2000). The results obtained point out that the Catholic Church has an important role regarding the thinking of language policies in the city once, in addition to offering Polish classes and using it in most masses and celebrations, it also occupies a space which is not used by the State as it also created the interchange project which has been developed in the State school. By following the projects it was possible to see that the issue of identity – the fact that most people are Polish descendents – is one of the main factors that motivate the participants to have more contact with this language. However, it was also concluded that there is shock between the community language and that considered standard Polish, which shows that the concept of language must be problematized, so that the project of teaching immigration languages seen as the result of language policy to support the use of this language does not have an inverse effect, that is, in order not to strengthen the monolingualism myth. Therefore, the study was developed with the hope to contribute with the discussions about situations which are sociolinguistically complex, so that the complexity inherent to language and identity relations is perceived.
Keywords: língua; identidade; Política(s) Linguística(s); language; identity; Language(s) Policy(ies); CNPQ::LINGUISTICA, LETRAS E ARTES::LINGUISTICA